Measuring Quality of Service (QoS) on Ki Hajar Dewantoro High School Internet Networks - Maesaroh, Siti; Hakim, Lukman; Erliyani, Ita; Hidayat, Khairul (Journal Collabits, 2024)
At SMA Ki Hajar Dewantoro Tangerang, the recurring issues with the internet network are attributed to several problems, including Throughput, Packet loss, Delay, and Jitter. By employing the Quality of Service (QoS) method, the values of these parameters can be measured to assess the performance of the existing internet services. The measurement of parameter values revealed the highest throughput during peak hours for ISP 1, with an average value of 1813 kbps falling into the 'Good' category. Conversely, the lowest throughput was observed during non-peak hours for ISP 2, with an average value of 300 kbps categorized as 'Poor.' The highest packet loss occurred during non-peak hours for ISP 2, with an average value of 1%, classified as 'Very Good.' On the other hand, the lowest packet loss was recorded during peak hours for ISP 1, with an average of 0.036%, categorized as 'Very Good.' Regarding delay, the highest average delay was noted during non-peak hours for ISP 2, with a value of 21.5ms falling into the 'Very Good' category. Conversely, the lowest delay was observed during peak hours for ISP 1, with an average value of 4.25ms categorized as 'Very Good.' For jitter, the highest average jitter occurred during non-peak hours for ISP 2, with a value of 21.5ms in the 'Good' category. In contrast, the lowest jitter was recorded during peak hours for ISP 1, with an average value of 4.25ms categorized as 'Good.'